ANALYZING THE EFFECTS OF LEARNING ENGLISH THROUGH LOCAL PROVERBS AND SAYINGS IN MULTILINGUAL COMMUNITIES (Modern education and development, 2025)
This study explores the impact of learning English through local proverbs and sayings in multilingual communities. It investigates how culturally familiar expressions can enhance learners’ understanding of idiomatic language, cultural context, and linguistic structures in English. By integrating local wisdom into English lessons, the research aims to highlight an innovative and context-sensitive approach to language acquisition that supports deeper cognitive and intercultural competence.